34 PATHFINDER; AN ALTERNATIVE TO THE EMERGENCY DEPARTMENT FOR OLDER PATIENTS WHO DIAL 999/112. (18th November 2021) - Bernard, P; Corcoran, G; Kenna, L; O'Brien, C; Ward, P; Howard, W; Hogan, L; Mooney, R
Abstract: Background: Traditionally in Ireland, people who dial 999/112 are transported to the Emergency Department (ED) unless they decline to travel. Many have non-urgent needs that could be treated elsewhere. Older people are particularly vulnerable to adverse events while in hospital. Alternative care pathway models can reduce ED crowding and improve patient outcomes. Methods: This service is a collaboration between the National Ambulance Service and Occupational Therapy (OT) and Physiotherapy Departments at a Dublin teaching hospital; funded by the Sláintecare Integration fund. It responds to low acuity 999/112 calls for people 65 years and older within the hospital catchment. The team operates Monday–Friday, a 'Rapid Response Team' (Advanced Paramedic and Physiotherapy/OT) (8:00–20:00) and a 'Follow-Up Team' (Physiotherapy and OT) (8:00–16:00). Once activated, the 'Rapid Response Team' conduct a comprehensive assessment in the home to establish whether a suitable alternative to the ED is available, commonly through the activation of one or more alternative care pathways (e.g. GP, Integrated Care Team, Primary Care Team, Community Intervention Team, Geriatric Day Hospital). Results: In the first year, 485 patients were responded to. Average age was 80 years, average Rockwood Clinical Frailty Scale score was 6 (moderately frail). The majority (68%) remained at home following initial review. Less than 1% re-presented within 24 hours, 9% re-presented within 7 days. The three most common reasons for dialling 999/112 were falls, generally unwell and non-traumatic back pain. Patient and care-giver feedback demonstrated a very high level of satisfaction with the service. Conclusion: This model is a safe alternative to the ED for older people following a low-acuity 999/112 call. Access to a network of alternative care pathways and immediate follow-up are two key enablers. The overwhelmingly positive feedback confirms that older people want this service. It is the first model of this kind to be evaluated in Ireland, and could expand, with local adaptation, nationally.